Performance and scalability analysis of monolithic and microservice architectures in social networks - Chernohor, Viacheslav (Journal of Computer Sciences Institute, 2025)
The article is focused on the research of the efficiency of using monolithic and microservice architectures in web applications. A comparative analysis of seven architectural configurations is made according to the following metrics: response time, resource consumption, number of processed requests, and cost of deployment in AWS. Docker, Postman, Prometheus, and Grafana were used to collect metrics. The results of the experiment allowed us to determine the optimal architectures for different load levels and formulate recommendations for choosing architectural solutions in modern systems.